A 5-year retrospective study of rampant dental caries among adult patients in a Nigerian Teaching Hospital - M Ajayi Deborah; M F Abiodun-Solanke Iyabode; O Gbadebo Shakeerah (Wolters Kluwer Medknow Publications, 2015)
Background: Rampant caries in adults has not been a focus of many researches unlike the childhood form of the disease. The disease is an interesting finding in an adult patient. When the condition occurs in children, it has been described as nursing bottle caries, baby bottle tooth decay, and the most recently adopted term, "early childhood caries". Aim: The aim was to determine the prevalence of rampant caries among adult patients. Materials and Methods: Cases of rampant caries were identified from the records of all the patients treated during a 5-year period. Variables considered included the socio-demographic data, frequency of consumption of cariogenic diet, social habits, decayed, missing, filled teeth (DMFT), socioeconomic status (SES), and oral hygiene (OH), etc. Data were analyzed using student's t-test and one-way ANOVA for continuous variables, while Fishers exact test was adopted for categorical variables. Level of significance was set at P < 0.05. Result: Less than 1% (21 out of 3458) of patients treated during the period had adult rampant caries, but only 17 patients with complete data were analyzed. The age range of the patients was 22-61 years with a median of 36 years. The number of teeth with open carious cavities ranged from 8 to 18, with a mean of 11.6 ± 3.3 teeth. A statistically significant difference was found in the number of open carious cavities and gender (P = 0.03), and between the SES and OH (P = 0.001). Patients in low SES had the poorest OH, The number of open carious lesion was higher in those that consumed refined sugar regularly. Conclusion: Occurrence of rampant caries was low and related to low socioeconomic status and regular consumption of cariogenic diet.